PENGARUH EKSTRAKULIKULER PALANG MERAH REMAJA (PMR) TERHADAP PSIKOMOTORIK SISWA DI MTSN 2 MATARAM - Zaki, Muhamad; M. Adam Imtiyaz; Latifatul Husna; Najwa Batrisyia Azizah Sudiarta; Karlina Oktaviana Putri; Junaidi, Junaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of extracurricular activities of the Youth Red Cross (PMR) on the psychomotor development of students at MTsN 2 Mataram. The psychomotor aspect includes fine and gross motor skills that develop through physical activity. PMR extracurricular at MTsN 2 Mataram has been around for more than 10 years and is very popular with students. PMR is designed to train skills such as First Aid, Family Care, Stretcher Making, Tent Assembling and Disaster Risk Reduction. Through these activities, students not only gain knowledge but also experience significant physical development. This study used a qualitative approach with data collection techniques through interviews with students, supervising teachers, and PMR trainers. The results showed that PMR activities have a positive impact on students' psychomotor development, both in fine motor and gross motor. Fine motor skills are improved through activities such as wound dressing and family care, while gross motor skills are developed through physical activities such as putting up and taking down tents. Challenges in implementation include limited training tools and variations in student abilities. Overall, PMR activities at MTsN 2 Mataram contribute significantly to students' psychomotor development. With improved facilities and school support, the benefits of PMR activities can be optimized. The results of this study are expected to be a reference.